Maritime students' views on coastal environmental conditions in Tanjung Pinang - T Jessica Eliyoni Yafia; Saputra Rama Rendra; Purba Reynaldi; Adinata Pria Apta (SHS Web of Conferences)
The provincial capital of the archipelagic Riau Islands, whose residents primarily reside in coastal areas, is Tanjungpinang. Environment on the coast. Tanjung Pinang's coastal environment is currently in poor condition; there is a lot of trash on the beach and in the water. There is a need for innovation and inspiration as well as efforts to protect the coastal ecosystem because tossing trash into the water can harm the coastal ecology. The first step in protecting the coastal environment is to avoid discarding trash into the ocean, particularly plastic waste. Other steps include planting mangrove trees and creating warning signs. The study's objective is to examine participants' knowledge of Tanjung Pinang's coastal environmental issues as well as their involvement in environmental protection. researchers collected data using qualitative techniques along the coast. Students majoring in English education made up 29 of the participants that contributed to the writing of this essay. The K1 and K2 classes were given a questionnaire, which the researchers utilized to collect data. Based to the findings of this study, many English language education students believe that the maritime conditions in Tanjung Pinang are very dirty, and they argue that it is the responsibility of all components of society, including the government, to keep the Tanjung Pinang maritime environment clean.